PARENTING DI PAUD SEBAGAI UPAYA PENDUKUNG TUMBUH KEMBANG ANAK USIA DINI - Tatik Ariyati (Khazanah Pendidikan, 2016)
Being parents who can take care their children are actually can be done by anyone as long as they are patient and willing to study. The wise parents will give significant effect toward the kids’ growth and development. In the future, they will be “someone” that is affected by their parenting. Normally, there are no parents who wish their children to have miserable and unhappy future. Unfortunately, the parents are not rarely found to make mistakes and it affects badly to them. It happened because of the parents’ lack of knowledge and understanding. Parenting plays a significant role for early childhood, when the parents educate their children very well, the parents educate them from the family environment, and parenting emphasizes the big role of family to them and gave the lesson to know themselves, as well as to know the family environment to form the kids’ character firstly. Parenting also helps children to find out their position based on their sex in the environment of family, society, and country. Parenting helps children to know the values or rules to make them follow the rules so that they can be accepted by the surrounding. Parenting also encourages children in search of worldly or hereafter science which is beneficial for their life. Parents also need to be on the watch for their intercommunication with mates or surrounding because there must be either positive or negative impact in it. Parents also need to give sincerely love to their children so that they never feel alone and lonely. Parenting should be given accordingly with the children’s ability to make them not in a force feeling with the parenting. Therefore, parenting has a significant role in educating early childhood. Keyword : parenting, early childhood education, early childhood growth and development.